Influence of Annealing Temperatures on Properties in Chelate Based CuI Thin Films - Zulkifly, Aziz; Ayib Rosdi, Zainun; Saifful Kamaluddin, Muzakir (Universiti Malaysia Pahang, 2016)
Copper(I) iodide (CuI) has received considerable scrutiny as a hole transport material in solid-state dye-sensitized solar cells (ss-DSSC), amidst challenging issues such as rapid crystallization, pore filing, and dye desorption. This paper would attempt to study the influence of heat on various properties of CuI thin film in the presence of chelating agent tetramethylethylenediamine (TMEDA) in the CuI precursor solution at fixed CuI:TMEDA molar ratio of 1:1. Although heat did not seem to alter the morphology of the thin film, slight broadening was observed in the diffractogram peaks which suggested reduction in particle size. Photoluminescence (PL) spectra for all the samples which were annealed below 80 ⁰C were red shifted which suggested than some of the absorbed energy has been lost most likely due to non-radiative emission usually caused by deep space traps. In other word, this finding also suggest that an optimum heating temperature would mend the material’s internal structure leading to fewer formation of deep space traps normally associated with the presence of internal stress in the material. At an optimum annealing temperature of 80 ⁰C, thin film resistivity fell from 6.2 Ω.cm to 4.7 Ω.cm and achieved a remarkable conductivity of 165 S/cm2. These remarkable findings seems to be in accord with our argument that CuITMEDA complex could find its application as a hole transport material (HTM) in ss-DSSC